A MATCH MADE IN HEAVEN: QUEER CHRISTIANS & DATING APPS - King, W.E. (AoIR Selected Papers of Internet Research, 2023)
Dating apps pose particular challenges for queer Christians, reproducing oppressions and experiences of dispossession in the context of seeking intimate relationships. Queer Christians using dating apps complicates an already sensitive combination of social and cultural commitments, values, and beliefs. Dating apps position themselves in the dating market in a variety of ways, however all function to help people meet other people for dates. Some apps are known for facilitating hookups or catering to queer populations, others are used more broadly and aim to facilitate long-term relationships. Dating apps, along with other social media sites, independently create and control the categories users interact with. On dating apps, users expect the app interface to enable them to represent their unique identities. However, dating apps are often designed with dominant populations in mind and end up excluding those who do not fit the model of their ideal user. Ultimately, my analysis reveals how queer Christians know and express gender and religious identities on dating apps but dating apps do not allow for this complexity to be easily visible or searchable. Queer Christians wrestle with dominant narratives, deviate from social scripts, and resist condemnation to a life without hope for loving partnerships. Dating apps offer fine-grained means of seeking and finding a match made in heaven while simultaneously constructing a hellhole of exclusionary, discriminatory, and oppressive binary categories. Still, queer Christians depend on dating apps, both to do queer identity work and to help them seek and find their match made in heaven.